Age-related physiological prerequisites for the formation of learning motivation - Yusupova , Xusniya; Musurmonkulova , Gulsanam (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article examines the age-related physiological prerequisites for the formation of learning motivation in children and adolescents. It analyzes the development of the nervous system, cognitive processes, and emotional-volitional sphere at different stages of ontogenesis. Special attention is given to the influence of biological factors on the development of interest in learning and the stability of motivation. The conclusion emphasizes the importance of considering age-related physiological characteristics in the educational process